The Actant and Functional Scheme of Greimas in the Short Story Wa Kanat Al-Dunya By Taufiq Al-Hakim : Narrative Semiotics of A.J. Greimas - Umami, Emma Asyirotul (Islah: Journal of Islamic Literature and History, 2023)
This study aims to analyze the short story Wa Kanat Al-Dunya in the anthology of short stories Arinillah by Taufiq al-Hakim with the theory of narrative semiotics A.J. Greimas. This research focuses on narratological analysis, also known as narrative theory. This research involves a literature study to collect research data. The researcher analyzed the data based on A.J. Greimas' theory of actant and functional schemes. The results of this study prove that this short story has six actant schemes in accordance with Greimas' theory, i.e., subject, object, sender, receiver, opponent, and helper. In the analysis, the author divides the story into three segments. From each segment, there are six actant schemes. The main actant resulting from the interconnection between one segment and another was found, i.e., the sender in the form of the actor's psychic inclination towards his desires. A very dominant Receiver is the 'devil'. In the Subject actants with a dominating role is also the character 'devil'. Furthermore, the object in this story is hatred towards Adam. Meanwhile, the character who plays the role of opponent is the 'sly snake'. The character 'sly snake' does not only act as an opponent but also as a helper for the subject. This research also discovered the functional structure in the short story which consists of the initial situation, transformation, and the final situation.